GAMBARAN ASUHAN KEPERAWATAN DALAM PEMENUHAN KEBUTUHAN RASA NYAMAN PADA PASIEN HIPERTENSI DENGAN NYERI AKUT DI RSUD ENDE - Paschalia, Yustina; Juwana , Emerensiana (Kelimutu Nursing Journal, 2024)
Hypertension is a condition where blood pressure increases beyond normal limits. A person is said to be hypertensive if they have systolic blood pressure > 140 mmHg and diastolic blood pressure > 90 mmHg, on repeated examinations. According to the World Health Organization (2022), the prevalence of hypertension in the world is 22% of the total world population, where there are 1.13 billion people in the world who suffer from hypertension. The incidence of hypertension is mostly in developing countries with low and middle incomes, including Indonesia (Doso, et al., 2019 in Jabani, Asriah Septiawati. et al. 2021). This study aims to describe the application of nursing care in fulfilling the comfort needs of patients with a medical diagnosis of hypertension. The method used in this research is a descriptive case study design with a nursing care approach which includes assessment, nursing diagnosis, nursing intervention, implementation and nursing evaluation. The subject of this research was a patient with a medical diagnosis of hypertension who was treated at RPD III Ende Regional Hospital. The results of the case study found that nursing problems related to the risk of ineffective cerebral perfusion were related to hypertension, acute pain was related to physiological injurious agents, activity intolerance was related to weakness, and disturbed sleep patterns were related to environmental obstacles. Nursing interventions and implementation in this research were designed and implemented in the form of dependent actions such as observation, education and interdependent actions such as collaborative actions. After implementing it for 3 days, all of these nursing problems could be resolved. It was concluded that it is important to apply nursing care to hypertensive patients holistically and professionally. It is recommended that patients and families continue to follow the recommendations given by health workers, so that the healing process can take place more quickly and prevent complications.